One size does not fit all: Selling firms to private equity versus strategic acquirers - Fidrmuc, Jana P.; Roosenboom, Peter; Paap, Richard; Teunissen, Tim (Journal of Corporate Finance, 2012)
This paper investigates the selling process of firms acquired by private equity versus strategic buyers. In a single regression setup we show that selling firms choose between formal auctions, controlled sales and private negotiations to fit their firm and deal characteristics including profitability, R&D, deal initiation and type of the eventual acquirer (private equity or strategic buyer). At the same time, a regression model determining the buyer type shows that private equity buyers pursue targets that have more tangible assets, lower market-to-book ratios and lower research and development expenses relative to targets bought by strategic buyers. To reflect possible interdependencies between these two choices and their impact on takeover premium, as a last step, we estimate a simultaneous model that includes the selling mechanism choice, buyer type and premium equations. Our results show that the primary decision within the whole selling process is the target firm's decision concerning whether to sell the firm in an auction, controlled sale or negotiation which then affects the buyer type. These two decisions seem to be optimal as then they do not impact premium.